Kelayakan Usaha Tani Bawang Merah pada Lahan Marginal Berpasir di M-25 Agro, Kecamatan Banguntapan, Kabupaten Bantul, Provinsi Yogyakarta - Prasetyo, Cahyo; Fachriyan, Hilmi Arija; Ni’mah, Lu’lu’a Ulyn; Subantoro, Renan (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The utilization of marginal sandy land for shallot (Allium cepa var. ascalonicum L.) cultivation has promising economic value and the potential to increase national food production. This study aims to analyze the feasibility of shallot farming on marginal sandy land at M-25 Agro, located in Sampangan Village, Banguntapan District, Bantul Regency, Yogyakarta Province, using the Revenue Cost Ratio (R/C Ratio) analysis approach to demonstrate that the business is viable and profitable. The results of the study show that the total cost incurred for shallot production on an area of 5000 m² at M-25 Agro reached IDR 16,658,333, while the total revenue generated amounted to IDR 100,000,000. With an R/C Ratio calculation of 6.00, this study concludes that the shallot farming business on the marginal sandy land is highly profitable and feasible to continue.